Effect of hospital ethical climate on the nurses' moral sensitivity - Cerit, Birgül; Özveren, Hüsna (The European Research Journal, 2019)
Objectives: The study determines the effects of the hospitals ethical climate on the moral sensitivity of nurses.Methods: The study design is descriptive and correlational. The data was obtained from 99 nurses who voluntarily accepted to fully participate in the surveys conducted. The data was analysed using descriptive statistics and Pearson correlations.Results: As a result of the study, the ethical climate perception of nurses and their moral sensitivity level was found to be above average. A positive, meaningful and medium relationship was found between the moral sensitivity level of nurses and ethical climate perceptions of nurses. Conclusions: Our findings support that the ethical climate perception of nurses is an important factor in determining the moral sensitivity. Consequently, building an ethical climate in all the hospitals that provide health care will result in a high moral sensitivity of nurses when giving health care.